2016
DOI: 10.1007/s10639-016-9493-x
|View full text |Cite
|
Sign up to set email alerts
|

Computer science in K-12 school curricula of the 2lst century: Why, what and when?

Abstract: In this paper we have examined the position and roles of Computer Science in curricula in the light of recent calls for curriculum change and we have proposed principles and issues to consider in curriculum design as well as identifying priority areas for further research. The paper is based on discussions within and beyond the International Federation of Information Processing (IFIP) Education Community since 2012 as well as an analysis of curriculum developments in five different countries. Emerging themes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
145
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 239 publications
(146 citation statements)
references
References 27 publications
0
145
0
1
Order By: Relevance
“…In summary the arguments outlined here present a strong case for the importance of Computer Science in the curriculum for 21st-century learning. Its importance for individual learners, in particular, leads to our recommendation that learning Computer Science is an entitlement for all school students and recent curriculum development takes this approach [14].…”
Section: Rationales For Computer Science In the Curriculummentioning
confidence: 99%
See 3 more Smart Citations
“…In summary the arguments outlined here present a strong case for the importance of Computer Science in the curriculum for 21st-century learning. Its importance for individual learners, in particular, leads to our recommendation that learning Computer Science is an entitlement for all school students and recent curriculum development takes this approach [14].…”
Section: Rationales For Computer Science In the Curriculummentioning
confidence: 99%
“…Therefore, in spite of the limited empirical evidence on which to base curricular design, many Computer Science curricula exist and many countries have recently re-designed Computer Science curricula. An analysis of developments in five countries as well as a review and content analysis of curriculum reports [14] suggested key issues to consider when designing Computer Science curricula. First there is a consensus across various curriculum reports [2,3,17] about the key concepts and techniques of the discipline.…”
Section: The Position Of Computer Science In the Curriculummentioning
confidence: 99%
See 2 more Smart Citations
“…The examples above illustrate, on the one hand, the lack of consensus on the definition of computational thinking [8] and, on the other hand, the difficulty of proposing concrete contents which respect teachers' freedom to suit to their specific school context. Experts recommend that the computing curricula should provide clear examples [9], being this the main contribution of this paper. The current work stems from an extensive on-field experience of four years of computational activities with a huge variety of 30 schools and more than 1000 students, figures significantly larger than those in the state of the art [10].…”
Section: Introductionmentioning
confidence: 99%